Occurrence, Phenotypic and Molecular Characteristics of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli in Healthy Turkeys in Northern Egypt - Amira A. Moawad; Helmut Hotzel; Hafez M. Hafez; Hazem Ramadan; Herbert Tomaso; Sascha D. Braun; Ralf Ehricht; Celia Diezel; Dominik Gary; Ines Engelmann; Islam M. Zakaria; Reem M. Reda; et al. (Antibiotics, 2022)
Poultry is one of the most important reservoirs for zoonotic multidrug-resistant pathogens. The indiscriminate use of antimicrobials in poultry production is a leading factor for development and dissemination of antimicrobial resistance. This study aimed to describe the prevalence and antimicrobial resistance of E. coli isolated from healthy turkey flocks of different ages in Nile delta region, Egypt. In the current investigation, 250 cloacal swabs were collected from 12 turkey farms in five governorates in the northern Egypt. Collected samples were cultivated on BrillianceTM ESBL agar media supplemented with cefotaxime (100 mg/L). The E. coli isolates were identified using MALDI-TOF-MS and confirmed by a conventional PCR assay targeting 16S rRNA-DNA. The phenotypic antibiogram against 14 antimicrobial agents was determined using the broth micro-dilution method. DNA-microarray-based assay was applied for genotyping and determination of both, virulence and resistance-associated gene markers. Multiplex real-time PCR was additionally applied for all isolates for detection of the actual most relevant Carbapenemase genes. The phenotypic identification of colistin resistance was carried out using E-test. A total of 26 E. coli isolates were recovered from the cloacal samples. All isolates were defined as multidrug-resistant. Interestingly, two different E. coli strains were isolated from one sample. Both strains had different phenotypic and genotypic profiles. All isolates were phenotypically susceptible to imipenem, while resistant to penicillin, rifampicin, streptomycin, and erythromycin. None of the examined carbapenem resistance genes was detected among isolates. At least one beta-lactamase gene was identified in most of isolates, where blaTEM was the most commonly identified determinant (80.8%), in addition to blaCTX-M9 (23.1%), blaSHV (19.2%) and blaOXA-10 (15.4%). Genes associated with chloramphenicol resistance were floR (65.4%) and cmlA1 (46.2%). Tetracycline- and quinolone-resistance-associated genes tetA and qnrS were detected in (57.7%) and (50.0%) of isolates, respectively. The aminoglycoside resistance associated genes aadA1 (65.4%), aadA2 (53.8%), aphA (50.0%), strA (69.2%), and strB (65.4%), were detected among isolates. Macrolide resistance associated genes mph and mrx were also detected in (53.8%) and (34.6%). Moreover, colistin resistance associated gene mcr-9 was identified in one isolate (3.8%). The class 1 integron integrase intI1 (84.6%), transposase for the transposon tnpISEcp1 (34.6%) and OqxB -integral membrane and component of RND-type multidrug efflux pump oqxB (7.7%) were identified among the isolates. The existing high incidence of ESBL/colistin-producing E. coli identified in healthy turkeys is a major concern that demands prompt control; otherwise, such strains and their resistance determinants could be transmitted to other bacteria and, eventually, to people via the food chain.